PENGARUH BORAKS TERHADAP KUANTITAS SPERMA MENCIT (Mus musculus) - Rosa, Yunilda (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2013)
The use of food additive such as borax has a negative effects on health, example the abuse of borax as food additive in the pempek and bakso can be dangerous for human health at Palembang city. The borax or boric acid have toxic effect on all body cells. The purpose of the research is to assess the effect of borax on the quantity of mice sperm, how many are the borax doses can cause decrease the quantity of sperm mice. The research was carried out at laboratory Department of Medical biology, Faculty of Medicine Sriwijaya University Palembang using a Completely Randomized Design. The treatment group give the borax, the control group was administrated by similar volume of aquabidest only. The result showed that borax could significantly decreased (P<0,05) the number of mice sperm concentration compared to control group. As a conclusion the administration of borax at doses 4 mg/10 gr bw and 6 mg/10 gr bw on male mice by gavage in 35 days can significantly decrease the quantity of mice sperm compared to the control group. It is suggested to conduct further studies such as the fertility test of mice sperm given borax longer than 35 days by gavage. Key words: Borax, The quantity of sperm and Mus musculus